Blind to Bias? Young Children Do Not Anticipate that Sunk Costs Lead to Irrational Choices. Issue 11 (11th November 2021) - Sehl, Claudia G.; Friedman, Ori; Denison, Stephanie
Abstract: Young children anticipate that others act rationally in light of their beliefs and desires, and environmental constraints. However, little is known about whether children anticipate others' irrational choices. We investigated young children's ability to predict that sunk costs can lead to irrational choices. Across four experiments, 5‐ to 6‐year‐olds (total N = 185) and adults (total N = 117) judged which of two identical objects an agent would keep, one obtained at a high cost or one obtained at a low cost. In Experiment 1, adults predicted that the agent would choose the high‐cost object over the low‐cost one, whereas children responded at chance. Experiment 2 replicated these findings in children, but also included another condition which showed they were sensitive to future costs. They predicted that an agent would be more likely to seek out a low‐cost item than a high‐cost item. Experiments 3 and 4 then found that children do not anticipate the sunk cost bias in first person scenarios, or in interpersonal sunk cost scenarios, where costs are sunk by others. Taken together, our findings suggest that young children may struggle to understand and predict irrational behavior. The findings also reveal an asymmetry between how they consider sunk costs and future costs in understanding actions. We propose that this asymmetry might arise because children do not consider sunk costs as wasted.